Application of Ordered Porous Silica Materials in Drug Delivery: A Review - Wenwen Liu; Junlin Wu; Zehao Jiang; Xinyu Zhang; Zhenxiang Wang; Fanjun Meng; Zidi Liu; Teng Zhang (Molecules)
Nanotechnology has significantly advanced various fields, including therapeutic delivery, through the use of nanomaterials as drug carriers. The biocompatibility of ordered porous silica materials makes them promising candidates for drug delivery systems, particularly in the treatment of cancer and other diseases. This review summarizes the use of microporous zeolites and mesoporous silica materials in drug delivery, focusing on their physicochemical properties and applications as drug carriers. Special emphasis is placed on strategies for encapsulation and functionalization, highlighting their role in enhancing drug loading and enabling targeted delivery. In conclusion, while ordered porous silica materials hold great potential for drug delivery systems, certain challenges remain.